Gender Mainstreaming at DPR RI during Period 2019–2024 - Ratna Wati; Mansyur Achmad; Dedeh Maryani; Wahyu Tri Putranto (Enrichment : Journal of Management, 2021)
The less percentage of women at the parliament will affects the DPR RI policies regarding women and their duties and functions as people's representatives. This research has purposes to investigated and compose a new method strategy that is useful to appliance efforts in order to achieve gender justice (Sexes) and gender equality at DPR RI. This research was conceived with a qualitative method based on positivism paradigm from 9 informants according to proposed criteria by snowball sampling technique. The data collection techniques used were literature study, interviews and observations which were analyzed using descriptive analysis and developed through the analysis of the observer's training. The research findings according to the Grindle public policy implementation model disclose that these gender mainstreaming policies enforcement at chores and roles from DPR RI is an adequate to aid the completion of gender parity and fairness in the life of society, nation and state, precisely to boost the women's function, status and capacity in the eyes of society both all aspects and levels. These enforcement of the gender-based policies in national development needs to be highlighted and expanded via official legality strategies, structural synergy strategies, cultural adaptation strategies and individual strengthening strategies.